TOPICAL ISSUES OF THE TAX SYSTEM IN THE PROCESS OF NATIONAL ECONOMY TRANSFORMATION (American Journal of Business Management, Economics and Banking, 2026)
This article examines the role and importance of the tax system in the process of national economy transformation from a scientific and practical perspective. The topical issues of improving the tax system under the conditions of deepening economic reforms, economic diversification, and increasing competitiveness are analyzed. Within the framework of the study, special attention is paid to the relationship between tax policy and economic growth, reforming tax administration, optimizing the tax burden, and the impact of the tax system on transformation processes. In addition, certain problems of existing tax mechanisms, the effectiveness of tax incentives, and issues related to expanding the tax base are highlighted. Based on the conducted analysis, scientific conclusions and practical recommendations aimed at improving the tax system to ensure sustainable development of the national economy have been developed.